2019
DOI: 10.1021/acsanm.9b00066
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Contact of Metals at the Nanoscale Overcomes the Oxidative Susceptibility of Silver-Based Nanobiosensors

Abstract: Silver (Ag) is one of the most sensitive noble metals for nanoplasmonic applications. However, Ag is prone to oxidation in wet environments (e.g., aqueous and organic solvents), which usually leads to poor adhesion between Ag and dielectrics, thereby limiting its use in biosensing applications. To address this challenge, we propose a new design principle where one metal corrodes preferentially when in electrical contact with the other metal, in the presence of an electrolyte. Specifically, by using a simple tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Bimetallic structures using silver and other metals also proved to be useful in other aspects, apart from increasing the sensitivity of sensory surfaces. In bimetallic Ag and titanium nanoislands on top of SiO 2 surfaces, Ti proved to suppress the Ag from its oxidation in wet environments of SPR structures [ 34 ]. A thin Cu seed layer was shown as an effective approach to produce atomically smooth Ag films with greater electrical conductivity [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic structures using silver and other metals also proved to be useful in other aspects, apart from increasing the sensitivity of sensory surfaces. In bimetallic Ag and titanium nanoislands on top of SiO 2 surfaces, Ti proved to suppress the Ag from its oxidation in wet environments of SPR structures [ 34 ]. A thin Cu seed layer was shown as an effective approach to produce atomically smooth Ag films with greater electrical conductivity [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the data point of view ( Figure 5 ), the mode 2 is the most suitable for sensing (sensitivity is 440.2 nm / RIU, FOM = 52.6), followed by the mode 4 (sensitivity is 353.9 nm/RIU, FOM = 18.7). The mode 2 achieves higher sensing performance than that of other plasmonic biosensors [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Although mode 4 is slightly inferior to mode 2 in sensitivity and FOM value, it is undeniable that mode 4 is also a resonance mode that is very suitable for sensing.…”
Section: Resultsmentioning
confidence: 99%
“…The maximal absorption rate of these three absorption peaks can reach 98.88%, 99.96%, and 99.17%, respectively. These are far superior to other non-metamaterial plasma sensors [ 23 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some aspects of nanomaterials, such as sensor surfaces constructed from metals like silver, represent limitations in the evaluation of TDM with optical biosensors. It has been observed that nanoparticles made of this material could be released from their surface by general oxidation to biofluids [190]. It is important to note that the development of nanomaterials for the construction of optical biosensors is a great challenge, such that these nano-scale particles cannot contaminate plasma samples from patients in a state where the determination of MDD is vital for a favourable clinical outcome.…”
Section: Discussionmentioning
confidence: 99%